Assessing neonatal care practices in rural Nepal - Rezai, Tania; Baral, Kedar; Koirala, Samir; Paudel, Sudarshan; Kache, Saraswati (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Child health indicators of under-five and infant mortality has improved in Nepal, but neonatal mortality remains high. The aim of this study is to assess neonatal care practices among mothers in rural Nepal.Methods: A household survey was conducted in the village of Daman in Makwanpur district, Nepal. All households that had an infant less than one year of age, and had been residing in Daman for greater than six months were included in the study.Results: There were 117 mothers with neonate assessed. The average age of mothers was 24 years and 39 (33.3%) were illiterate, 53 (45.3%) were home births and 36 (30.8%) births were registered. Ninety seven (82.9%) neonates cried immediately after birth, 95 (81.1%) used a new or boiled blade for umbilical cord, 20 (16.7%) applied oil to the cord stump and 71 (61%) breastfed within first hour of birth. There was a significant relationship between non-exclusive breastfeeding and sickness.Conclusions: In Daman village community awareness for umbilical cord care and breastfeeding after birth was high. For thermal regulation of the infant, more health education is required.Journal of Patan Academy of Health Sciences, Vol. 2, No. 2, 2015. page: 23-27